2014
DOI: 10.1080/00380768.2014.949854
|View full text |Cite
|
Sign up to set email alerts
|

Selective induction of putative iron transporters,OPT8a and OPT8b, in maize by mycorrhizal colonization

Abstract: Arbuscular mycorrhizas support nutrient uptake from the soil. Here we demonstrated Iron-59 ( 59 Fe) uptake in maize (Zea mays L.) through the mycorrhizal roots. Arbuscular mycorrhizal colonization did not strongly induce Strategy II-related genes, but the putative iron transporter genes, OPT8a and OPT8b, were induced by more than 50-fold. Our data provide a previously undescribed gene expression mode related to the iron uptake system of Strategy II plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 28 publications
2
13
0
1
Order By: Relevance
“…Although the main benefit of the AM association is an improved P status of the mycorrhizal plant, AM fungi also play a role in Fe nutrition of their host plants (Clark and Zeto, 1996;Liu et al, 2000;Chorianopoulou et al, 2015). Direct evidence of the capability of the extraradical mycelium (ERM) to take up Fe from the soil and to transfer it to the host plant comes from studies using 59 Fe as a tracer in compartments only accessible by the external hyphae (Caris et al, 1998;Kobae et al, 2014). Conversely, other studies have shown that AM fungi play a role in reducing Fe uptake when the soil concentration is high (Liu et al, 2000;Juwarkar and Jambhulkar, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the main benefit of the AM association is an improved P status of the mycorrhizal plant, AM fungi also play a role in Fe nutrition of their host plants (Clark and Zeto, 1996;Liu et al, 2000;Chorianopoulou et al, 2015). Direct evidence of the capability of the extraradical mycelium (ERM) to take up Fe from the soil and to transfer it to the host plant comes from studies using 59 Fe as a tracer in compartments only accessible by the external hyphae (Caris et al, 1998;Kobae et al, 2014). Conversely, other studies have shown that AM fungi play a role in reducing Fe uptake when the soil concentration is high (Liu et al, 2000;Juwarkar and Jambhulkar, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fungal contribution to Fe uptake, expression of ZmYS1 encoding the transporter that mediates the uptake of PS-Fe(III) complexes from the rhizosphere was not affected in mycorrhizal roots. However, two oligopeptide transporter genes that were proposed to mediate the transport of Fe or Fe-complexes were highly induced in mycorrhizas (Kobae et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Phenolics have also been identified in Fe-deficiency-induced root exudates ( Jin et al, 2014 ), although the precise constituents remain poorly understood. Additional complexities arise when plants are mycorrhizal; in maize, for instance, strong induction of two Fe transporters, OPT8a and OPT8b , bypassing Strategy II, by mycorrhizal colonization was documented ( Kobae et al, 2014 ). Thus, much needs to be learned about rhizospheric microbial partners and their roles in Fe acquisition.…”
Section: Physiological Changesmentioning
confidence: 99%
“…irregularis (Kobae et al 2014b) was used to amplify the DNA fragments by PCR with the specific primers 5' -GCTCGAGATGTTACGGTATTCAAGTCCATTAGTTCA -3' and 5' -AGTCGACTTAAATAGCATCCGAGTTAGTCTCACCAC -3'. The amplified gene was ligated into pCR-Blunt II-TOPO vector (Life Technologies) and sequenced.…”
Section: Heterologous Expression Of Ringt In S Cerevisiaementioning
confidence: 99%